The dilemma of cost methods and cost management tools: A conceptual proposal (Research, Society and Development, 2021)
Important advances in accounting science were closely linked to those of society and companies, especially after the 19th century, when the improvement of cost calculation techniques became evident and necessary. Since then, notable contributions have emerged and account for the substrate of this conceptual line, until today. However, there is no evidence in the national and international literature, theoretical studies that present an objective separation between Costing Methods and Management Tools. The verification of the lack of studies that consider the Cost Management Tools as complementary elements to the Costing Methods seeks to answer the questions: How are the Costing Methods and the Management Tools treated in the studies? What is the methodological trend used in studies that address the theme costs? How often are Costing Methods and Management Tools used in studies? The article makes a classic separation of the theoretical concepts of Costing Methods and Cost Management Tools. The Cost Management Tools are different from the Costing Methods and, when chosen by the researcher, they can be used in a complementary way to the Costing Methods, supplanting the rigor of the analyses; and providing a greater degree of security in the calculation of costs, with a view to decision-making.